Nutrition and Diet Therapy - Cataldo, Corinne Balog (Wadsworth Publishing Company, 1998)
Organized by diets rather than organ systems or disease states, this text includes margin definitions, key points, self-check quizzes, self-studies, case studies and question-and-answer style "Nutrition in Practices"